IMPLIKASI OPERASIONAL BANK KELILING TERHADAP EKSISTENSI KOPERASI PENGUSAHA BATIK TEMBAYAT KECAMATAN BAYAT-KLATEN (Studi Empirik dalam Mekanisme Penyaluran Kredit) - Sutrisno Badri; C N Actini (Orasi Bisnis : Jurnal Ilmiah Administrasi Niaga, 2012)
Cooperative has three procedures in channeling credit the loan application procedure, loans research procedures, and procedures for loan disbursement. With these procedures take a long time, while prospective customers want fast service to get cash money, this is the weakness in developing cooperatives. The purpose of this study was to identify: (1) The effect of the existence (presence) Roving Bank to decrease the number of debtors in the Cooperative Employers Batik Tembayat (PBTt) Bayat Klaten. (2) Identifying the factors that influence the decrease in the number of debtors. Following data collection techniques: observation, interview or interviews, literature study, questionnaire, by distributing questionnaires to the borrowers about their relationship with the presence of the Bank Roving. Variable measurement scales used Guttman scale. Analytical techniques used in this study were: (1). Qualitative analysis is descriptive method that represents the state of the subject and object of research at the present time based on the facts available. (2). Quantitative analysis based on observational expectation (hope researcher) or customize goodness test (chi-square). The results showed: (1.) There is no influence of the presence of the Bank Roving with decreased number of debtors in the Cooperative PBT evident from the results of statistical analysis using Chi Square test statistic obtained value of 0.61 observed no larger than the expected value is 3.841. (2). Decrease the amount of the debtor's going on Cooperative PBT PBT more because of the lack of attention to the conditions of competition and marketing is happening now. (3). Shortage affecting members lack the capital for cooperatives so urgently needs external funds (non-members).